Trzykrotny „półkownik” III RP. Rzecz o współczesnej cenzurze na przykładzie filmu Witajcie w życiu Henryka Dederki - Krakowiak, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The 1990s in Poland were mainly a period of change caused by system transformation. The consequences of the new system were impoverishment, unemployment and exclusion. In the film context, an important result was that the Main Office for the Control of the Press, Publications and Performances was put into liquidation, thus abolishing official censorship. This difficult time for Poles was reflected in domestic cinematography. One of the most famous documentary films was Witajcie w życiu (Welcome to Life, 1997) by Henryk Dederko, portraying the society of the time intoxicated by the luminous vision of the future offered by the American corporation Amway. The article attempts to reconstruct the production and distribution adventures of Dederko’s film. The aim is to clarify cases concerning the numerous lawsuits brought against the filmmakers by Amway Polska and Network Twenty-One. The work is based on a reception and distribution study as well as a textual analysis. It also employs interviews with the director and producer, mentions in the press and articles, and, importantly, court documents from the Jacek Gwizdała Archive.